A Study of Achievement in English on The Surrounding Vocabulary of Prathomsuksa 5 Students by Cooperative Learning Using CIRC Technique - Limthong, Wititta (Journal of Dhamma for Life, 2025)
This study aimed to examine and compare the English vocabulary achievement of Grade 5 students before and after implementing cooperative learning using the CIRC (Cooperative Integrated Reading and Composition) technique. The sample consisted of 30 Grade 5/1 students selected through cluster sampling. Research instruments included 12 lesson plans on English vocabulary and a 40-item multiple-choice achievement test with a reliability coefficient (Cronbach’s alpha) of 0.85. Data were analyzed using descriptive statistics including percentage, mean, and standard deviation, as well as dependent sample t-test to compare pre- and post-test scores. The findings revealed that 100% of students achieved scores above the passing criterion after the intervention. Additionally, the post-test mean scores were significantly higher than the pre-test scores at the 0.05 level of significance. These results indicate that cooperative learning using the CIRC technique effectively enhances Grade 5 students’ English vocabulary achievement. It is recommended that this technique be applied in other teaching contexts to improve student learning outcomes.